Kewenangan Partai Politik dalam Mengusulkan Pemberhentian dan Penggantian Antar Waktu Anggota Dewan Perwakilan Rakyat Daerah (Studi Kasus Pemberhentian Nofrizon Sebagai Anggota DPRD Sumbar 2019-2024) - Muammar Kadafi Siregar; Azmi Fendri; Hengki Andora (Dinasti Research, 2024)
On April 27 2023, the Democratic Party DPP issued DPP Decree No. 104/SK/DPP.PD/IV/2023 concerning the Dismissal of Democratic Party Members. Nofrizon was terminated because he violated Organizational Regulation Number 01/PO/DPP.PD/VII/2019 Article 5 Paragraph 4 that Democratic Party members are obliged to obey and carry out the decisions of the faction leadership without exception. Then, through a letter from the Democratic Party of West Sumatra Province DPD No.12/ext/DPD.PD/SB/V/2023, dated 29 May 2023, the Democratic Party stated that Mr. Nofrizon had been permanently terminated as a member of the Democratic Party and proposed an interim replacement (PAW ) Member of the West Sumatra Province DPRD from the Democratic Party Fraction for the 2019-2024 period. The legal basis used as a process for the temporary termination and placement of West Sumatra Province DPRD members is Law Number 23 of 2014 concerning Regional Government Article 139 Paragraph (2) DPRD members are dismissed from time to time for reasons as specified in letters e, h and i as following e. Proposed by the political party in accordance with the provisions of the statutory regulations, h. Dismissed from being a member of the political party in accordance with the provisions of the statutory regulations; and I. Become a member of another Political Party. To answer this problem, it is necessary to formulate it into three problem formulations. First, what is the process for the interim termination of DPRD members? Second, what is the interim placement process for DPRD members? Third, what is the authority of political parties in promising the dismissal and temporary placement of DPRD members? This research is a type of legal research using a sociological juridical legal research approach. The results of this research show that the temporary dismissal of DPRD members due to such termination can be carried out through a decision of the Honorary Board and/or through a proposal from a political party. Bro. Nofrizon, S. Sos was temporarily dismissed as a member of the West Sumatra Province DPRD from the Democratic Fraction. This interim suspension was at the suggestion of the Political Party (Democratic Party) due to a change of party and not a personal resignation, through the Democratic Party DPP decision letter No.104/SK/DPP.PD/V/2023. The interim replacement process for Provincial DPRD members cannot be separated from the process of dismissal of DPRD members which occurs first. Political parties have the authority to stop the temporary dismissal of DPRD members, but the process of guaranteeing candidates for interim replacement names for Provincial DPRD members is the attributive authority of the Provincial KPU.